Methodology of Cryotherapy Use in Medical Practice - Panchenko, Oleg A. (Problems of Cryobiology and Cryomedicine, 2019)
Here, we studied the application efficiency of the whole-body extreme air cryotherapy in treatment of patients.Â The persons with borderline mental disorders demonstrated a decrease in asthenic disorders (66.4%), neuro-mental stressÂ (82.8%), trait and state anxiety (44.9 and 67.2%, respectively), improved well-being (36.2%), mood (31%), and increasedÂ activity (43.1%). Quite a complete or partial regression of cephalic syndrome (78.8 and 21.2%, respectively), no vestibulocerebellarÂ syndrome (68.2%), partial regression (31.8%) were revealed in patients with vascular pathology. Patients with musculoskeletal diseases had a decreased or levelled pain syndrome (100 and 77.7%, respectively), as well as reducedÂ clinical and neurological manifestations (78.6%), an increase in daily motor activity (94.3%), diminished restriction in standingÂ and walking (94.3%). The individualization of cryotherapy in aÂ combined rehabilitation therapy for patients with thisÂ pathology has enabled improving the treatment efficiency and reducing the therapy terms at the minimum drug cost. Â Probl Cryobiol Cryomed 2019; 29(2):137â€“147.